2021
DOI: 10.1101/2021.02.16.431524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual restoration fails to recover unconscious processing for smooth eye movements after occipital stroke

Abstract: Visual pathways that guide actions do not necessarily mediate conscious perception. Patients with primary visual cortex (V1) damage lose conscious perception but often retain unconscious abilities (e.g. blindsight). Here, we asked if saccade accuracy and post-saccadic following responses (PFRs) that automatically track target motion upon saccade landing are retained when conscious perception is lost. We contrasted these behaviors in the blind and intact fields of 8 chronic V1-stroke patients, and in 8 visually… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 125 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…It appears that PFR, as a smooth eye movement, follows the same distinction from perception. A recent study from our lab investigating recovery of motion perception in cortically-blind patients with V1 lesions found that improvements in perception did not correlate with any recovery of PFR in the blind fields, even when perception recovered to normal levels (Kwon et al, 2022). In fact, they found no significant PFR in blind-fields, suggesting that it must rely on motion signals that pass through area V1.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that PFR, as a smooth eye movement, follows the same distinction from perception. A recent study from our lab investigating recovery of motion perception in cortically-blind patients with V1 lesions found that improvements in perception did not correlate with any recovery of PFR in the blind fields, even when perception recovered to normal levels (Kwon et al, 2022). In fact, they found no significant PFR in blind-fields, suggesting that it must rely on motion signals that pass through area V1.…”
Section: Discussionmentioning
confidence: 99%